2022
DOI: 10.1111/aphw.12349
|View full text |Cite
|
Sign up to set email alerts
|

Predicting COVID‐19 booster vaccine intentions

Abstract: Achieving broad immunity through vaccination is a cornerstone strategy for long‐term management of COVID‐19 infections, particularly the prevention of serious cases and hospitalizations. Evidence that vaccine‐induced immunity wanes over time points to the need for COVID‐19 booster vaccines, and maximum compliance is required to maintain population‐level immunity. Little is known of the correlates of intentions to receive booster vaccines among previously vaccinated individuals. The present study applied an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 65 publications
7
29
1
Order By: Relevance
“…Interestingly, even in different study samples, behavioral control showed consistent significance, which revealed behavioral control as a powerful predictor of COVID-19 vaccination intentions. Recently, in a booster vaccination study, attitude and subjective norms were also found to be related to intentions [ 54 ]. In order to enhance uptake of the vaccine to ensure herd immunity, and reduce the incidence of severe cases, the public health departments should raise parents’ health beliefs and social responsibility through positive publicizing of the effectiveness and social worth of the vaccine booster.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, even in different study samples, behavioral control showed consistent significance, which revealed behavioral control as a powerful predictor of COVID-19 vaccination intentions. Recently, in a booster vaccination study, attitude and subjective norms were also found to be related to intentions [ 54 ]. In order to enhance uptake of the vaccine to ensure herd immunity, and reduce the incidence of severe cases, the public health departments should raise parents’ health beliefs and social responsibility through positive publicizing of the effectiveness and social worth of the vaccine booster.…”
Section: Discussionmentioning
confidence: 99%
“…While vaccine hesitancy has been extensively explored before the COVID-19 pandemic, research on booster vaccine hesitancy, particularly for COVID-19, is limited. With accounts of potentially new COVID-19 variants requiring the adaptation of existing vaccines and repeated doses [ 14 ], promulgation of anti-vaccination beliefs, conspiracies and misinformation on social media [ 15 ], as well as reports of the decreased severity of Omicron and waning vaccine immunity [ 16 ], hesitancy involving booster doses warrants investigation. While the development and availability of primary COVID-19 vaccines were eagerly anticipated in the early stages of the pandemic, with a more stable epidemiological profile and natural immunity conferred by infection rates, hesitancy and reluctance to undergo repeated COVID-19 booster vaccinations may become a challenge in maintaining sufficient immunization coverage against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that information need, subjective norms, perceived risk, and information channels can affect COVID-19 vaccine willingness, but they did not ask participants explicitly about exposure to the concerning news. 12,21,22,24,25,29,30,[33][34][35][36] The effect of exposure to concerning news on willingness to receive a booster dose is an area that needs further research especially with the introduction of new vaccines. Our nding may be related to explicitly asking respondents about the news they had consumed in recent months.…”
Section: Discussionmentioning
confidence: 99%